The effect of bimodal model on the ultra-broad temperature stable BaTiO3–Na0.5Bi0.5TiO3–Nb2O5 system. (15th March 2016) - Li, Lingxia; Zhang, Bowen
Abstract: A new lead-free, high dielectric constant, wide temperature stable dielectric ceramics was prepared by traditional solid-state method. The phase contribution, electric and dielectric properties of the BaTiO3 –Na0.5 Bi0.5 TiO3 –Nb2 O5 ceramics were investigated. The bimodal model was proposed to explain the phenomenon of ultra-broad temperature stable. The doping of CoO played a decisive role in the realization of a wide temperature range of − 50–350 °C stability. In addition, a relative higher dielectric constant and lower dielectric loss (εr  = 1365 ± 15%, tanδ = 1.513%) were obtained. These features suggest that the ceramics system can be considered as a promising candidate material for the next generation of MLCC. Graphical abstract: In this paper, the BaTiO3 –Na0.5 Bi0.5 TiO3 –Nb2 O5 (referred to as BNN) system doped with CoO was investigated. Moreover, the bimodal model is proposed and the microscopic mechanism of the model is analyzed.